Surface modification method of Co-CeO2 abrasive based on coordination of silane coupling agent and surfactant

By synergistically modifying the ceria abrasive with silane coupling agent and surfactant, the problem of insufficient dispersion and polishing effect of ceria nanoparticles is solved, and efficient polishing rate and surface quality improvement is achieved.

CN120248831APending Publication Date: 2025-07-04HEBEI UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510432778.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

In the prior art, the dispersion and polishing effect of cerium oxide nanoparticles are difficult to improve simultaneously, the silane coupling agent modification effect is single, and the surfactant modification may cause surface defects.

Method used

The silane coupling agent and surfactant are used to introduce active sites on the surface of ceria through silane coupling agent, and ionization of surfactant is used to generate anions to enhance electrostatic repulsion, achieving high dispersion of nanoparticles.

Benefits of technology

The dispersion and polishing quality of ceria abrasives have been significantly improved, the polishing rate has been increased by about 40%, and the surface quality has been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248831A_ABST
    Figure CN120248831A_ABST
Patent Text Reader

Abstract

The invention relates to a surface modification method of a Co-CeO2 abrasive material based on coordination of a silane coupling agent and a surfactant. According to the method, in the modification of the chemically mechanical polished cerium dioxide abrasive, different types of surfactants are added by utilizing a method of combining a silane coupling agent and the surfactants, and more active sites are introduced on the surface of cerium dioxide through the silane coupling agent, so that the surface of the cerium dioxide is modified. And meanwhile, the surfactant is ionized to generate anions, so that the electrostatic repulsion among the nanoparticles is enhanced, the dispersity of the cerium dioxide abrasive is enhanced, and the polishing rate and the polishing quality are further improved. When the obtained material is used as an abrasive material, the removal rate is increased to # imgabs0 #, and compared with a traditional abrasive material, the removal rate is increased by about 40%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polishing abrasives, and particularly to a surface modification preparation method based on cobalt-doped cerium oxide abrasives. Background Art

[0002] Cerium oxide nanoparticles play an important role in fields such as catalysis, energy storage, and chemical mechanical polishing due to their remarkable redox properties and high chemical stability. During the chemical mechanical polishing process, the good dispersibility of cerium oxide nanoparticles ensures the uniformity of the applied force during polishing, thus avoiding irregular polishing effects caused by particle aggregation. In addition, the particle size also has a significant impact on the polishing effect, and smaller-sized particles usually exhibit better polishing performance. Therefore, optimizing the dispersion of cerium oxide nanoparticles is a key factor in improving the quality and efficiency of chemical mechanical polishing.

[0003] Surface modification has become a key technology for enhancing the dispersion of nanoparticles. Its main goal is to improve the dispersibility and stability of nanoparticles in a liquid environment by adjusting their surface properties. Common modification methods include silane coupling agent modification and surfactant modification. Silane coupling agent modification can increase more active sites. For example, in "Understanding the role of oxygen vacancy on corrosion resistance of coating containing cerium oxide nanoparticles doped with cobalt as highly effective corrosion inhibitors" (http: / / doi.org / 10.1007 / s12541-022-00687-2), nano cobalt-doped CeO2 was prepared by the sol-gel method, and the surface was modified with KH-560 to improve the corrosion resistance of the coating and increase the oxygen vacancy content, but the modification effect is relatively single. Surfactant modification mainly enhances the electrostatic repulsion of CeO2 abrasives through hydrophilic groups. For example, in "Novel surface modification strategies for enhanced CeO2 nanoparticle dispersion and suspension stability" (http: / / doi.org / 10.1016 / j.ceramint.2024.04.216), two surfactants, TEOS and CTAB, were used to modify the surface of CeO2 respectively, and the dispersion state of CeO2 was significantly improved after modification, but it may cause surface defects. Summary of the Invention

[0004] The object of the present invention is to provide a surface modification method of Co-CeO2 abrasive based on the synergism of silane coupling agent and surfactant in view of the limitations existing in the current technology. In the modification of cerium dioxide abrasive for chemical mechanical polishing, a method combining silane coupling agent and surfactant is used, and different types of surfactants are added. By introducing more active sites on the surface of cerium dioxide through the silane coupling agent, and at the same time, the anions generated by the ionization of the surfactant enhance the electrostatic repulsion between nanoparticles, so as to enhance the dispersibility of cerium dioxide abrasive and further improve the polishing rate and polishing quality. The material obtained by the present invention is used as an abrasive, and the removal rate is increased to Compared with the traditional abrasive, it is increased by about 40%.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A surface modification method of Co-CeO2 abrasive based on the synergism of silane coupling agent and surfactant, the method comprising the following steps:

[0007] Step 1: Mix toluene and a silane coupling agent alkane solution and ultrasonicate for 10 - 30 min to obtain a first mixed solution;

[0008] Wherein, the volume ratio is that toluene : silane coupling agent solution = 15:1 - 25:1; the mass percentage concentration of the silane coupling agent solution is 40 - 60%;

[0009] Step 2: Under water bath, heat the first mixed solution to 80 - 100 °C and stir at this temperature for 15 - 20 minutes;

[0010] The stirring speed is 150 - 200 rmp;

[0011] Step 3: Then add Co-CeO2 and react for 8 - 10 hours;

[0012] Wherein, 10 - 20 g of Co-CeO2 is added to every 200 - 400 mL of the mixed solution;

[0013] Step 4: After the reaction is completed, filter, wash, and vacuum dry to obtain substance A;

[0014] Substance A is Co-CeO2-NH2 or Co-CeO2-SH;

[0015] Step 5: Mix substance A and a surfactant in distilled water and ultrasonicate for 20 - 40 minutes to obtain a second mixed solution;

[0016] Wherein, the mass ratio of substance A to the surfactant is 4 - 5:1; 10 - 20 g of substance A and 2 - 4 g of the surfactant are added to every 200 ml of distilled water;

[0017] Step 6: Under a water bath again, heat the second mixed solution to 80 - 100 °C, and stir at this temperature for 7 - 8 hours;

[0018] Step 7: Filter, wash, and dry under vacuum to obtain the modified Co - CeO₂ abrasive.

[0019] The washing in Step 4 and Step 7 is to wash successively with absolute ethanol and deionized water.

[0020] The silane coupling agent is ureidopropyltrimethoxysilane, mercaptopropyltrimethoxysilane, or mercaptopropyltriethoxysilane.

[0021] The surfactant is dialkyl sulfosuccinate, surfactant alkyl sulfonatoacetate, hydroxyethyl sulfonate, sulfonated fatty acid methyl ester, oligoglycerol, oligomeric (ethylene glycol) ester of fatty acid, ester quaternary ammonium salt, sodium dodecyl sulfate, sodium lauryl polyoxyethylene ether sulfate, dodecyl phosphate, or lauryl phosphate.

[0022] The application of the Co - CeO₂ abrasive prepared by the described method is used for the polishing of the SiO₂ dielectric layer.

[0023] Specifically, it includes the following steps:

[0024] (1): Disperse Co - CeO₂ - NH₂ - SS by wet ball milling, adjust the pH to 5 - 6 with KOH and acetic acid, and measure the concentration of the CeO₂ abrasive to be 0.5 - 1.5 wt%.

[0025] (2): Polish the TEOS wafer on a GNP polishing machine. The down - pressure is 2 - 4 psi, the back - pressure is 0 psi, the rotational speed of the polishing head and the polishing pad is 50 - 150 rpm, and the flow rate of the polishing liquid is 100 - 200 ml / min.

[0026] The substantial features of the present invention are:

[0027] The present invention aims to modify in two steps by combining a silane coupling agent and a surfactant. By exerting the synergistic effect of the two modifying reagents, the dispersion stability and wettability in the polishing liquid are improved to obtain a better polishing effect. Among them, the silane coupling agent has an amide group or a mercapto group at one end, including ureidopropyltrimethoxysilane, mercaptopropyltrimethoxysilane, etc. The surfactant includes sodium stearate containing an ester group, sodium dodecyl sulfate and sodium lauryl polyoxyethylene ether sulfate containing a sulfonate group, dodecyl phosphate and lauryl phosphate containing a phosphate group, etc. The two - step modification method combining the two types of reagents not only increases the content of Ce 3+ but also improves the dispersion stability and wettability of the polishing liquid, optimizes the particle size distribution, and obtains a better polishing effect.

[0028] The beneficial effects of the present invention are as follows:

[0029] The present invention uses cobalt-doped cerium dioxide as the base abrasive, and for the first time, modifies Co-CeO2 with a silane coupling agent and conducts a secondary modification with a surfactant, increasing the content of Ce in the Co-CeO2 abrasive and simultaneously enhancing the wettability and dispersibility of the abrasive. That is, the average Zeta potential of Co-CeO2 is -11.99 mV, while after modification with the silane coupling agent, the Zeta potential drops to -14.6 mV. After modification with the surfactant, the Zeta potentials of Co-CeO2-NH2-SS, Co-CeO2-NH2-SDS, and Co-CeO2-NH2-AES in the polishing liquid are -31.4 mV, -19.67 mV, and -17.54 mV respectively, and the Zeta potential further decreases, indicating that the dispersibility of the modified abrasive has been improved. 3+ The results of the polishing experiment tests show that the cerium dioxide abrasive after modification has good surface quality and a fast removal rate. The polishing rate of Co-CeO2 before modification is

[0030] After one modification, the polishing rate of Co-CeO2-NH2 has increased by nearly 30% and reached After the second modification, the removal rate of the Co-CeO2-NH2-AES abrasive has increased to which is about 40% higher than that of the traditional abrasive. The surface roughness (Sq) of Co-CeO2 before modification is 0.0819, and the surface roughness of the Co-CeO2-NH2-SS abrasive after the second modification has dropped to 0.0383, indicating that the polishing rate and surface quality of the modified abrasive have been improved. The preparation method adopted by the present invention is relatively mild and suitable for large-scale industrial production.

[0031] BRIEF DESCRIPTION OF THE DRAWINGS BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the FT-IR spectra of Co-CeO2, Co-CeO2-NH2, Co-CeO2-NH2-SS, Co-CeO2-NH2-SDS, and Co-CeO2-NH2-AES prepared in Examples 1-6;

[0033] Figure 2 is the C1s XPS spectra of the ureidopropyltriethoxysilane prepared in Examples 1-6;

[0034] Figure 3 is the C1s XPS spectra of Co-CeO2-NH2 prepared in Examples 1-6;

[0035] Figure 4Zeta potential diagrams of Co-CeO2, Co-CeO2-NH2, Co-CeO2-NH2-SS, Co-CeO2-NH2-SDS, and Co-CeO2-NH2-AES prepared in Examples 1-6;

[0036] Figure 5 Scanning electron microscope photos of Co-CeO2-NH2 prepared in Examples 1-6;

[0037] Figure 6 Scanning electron microscope photos of Co-CeO2-NH2-SS prepared in Examples 1 and 2;

[0038] Figure 7 Scanning electron microscope photos of Co-CeO2-NH2-SDS prepared in Examples 3 and 4;

[0039] Figure 8 Scanning electron microscope photos of Co-CeO2-NH2-AES prepared in Examples 5 and 6;

[0040] Figure 9 Surface quality after polishing of Co-CeO2-NH2 prepared in Examples 1-6;

[0041] Figure 10 Surface quality after polishing of Co-CeO2-NH2-SS prepared in Examples 1 and 2;

[0042] Figure 11 Surface quality after polishing of Co-CeO2-NH2-SDS prepared in Examples 3 and 4;

[0043] Figure 12 Surface quality after polishing of Co-CeO2-NH2-AES prepared in Examples 5 and 6; Detailed implementation manners

[0044] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0045] Example 1

[0046] Add 300 ml of toluene to a flask, mix it with 15 ml of 50 wt% ureapropyltriethoxysilane solution, and then ultrasonicate for 10 min. Place the flask in a water bath, raise the temperature to 80 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm for 15 min. Finally, add 15 g of Co-CeO2 to the flask, react for 8 h, filter after the reaction, wash successively with absolute ethanol and deionized water, and dry in vacuo. The resulting dry powder is amino-modified cerium oxide, denoted as Co-CeO2-NH2. Mix 10 g of Co-CeO2-NH2 nanoparticles with 2 g of the surfactant sodium stearate in 200 ml of distilled water at a mass ratio of 5:1. After ultrasonication for 30 minutes, place the flask in a water bath, raise the temperature to 85 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm, and react for 8 h. Filter after the reaction, wash successively with absolute ethanol and deionized water, and dry in vacuo. The resulting dry powder is surfactant-modified cerium oxide, denoted as Co-CeO2-NH2-SS.

[0047] As Figure 1 , Figure 2 and Figure 3 shown, the absorption peak intensities at 1525 cm -1 (-N-H) and 3410 cm -1 (-C-N) of Co-CeO2-NH2 increased significantly, indicating that the introduction of amino groups enhanced the interaction between surface hydroxyl groups and amino groups significantly, confirming that the grafting of silane coupling agents with amide groups or mercapto groups at the end on the surface of Co-CeO2 was achieved by the first modification. The absorption peaks at 2850 cm -1 and 2920 cm -1 showed obvious enhancement, attributed to the presence of -C-H, indicating that the surfactant molecules containing ester groups were successfully grafted onto the surface of Co-CeO2-NH2 after the second modification. As Figure 4 shown, the absolute value of the Zeta potential became larger after the two modifications, and the electrostatic repulsion between the two nanoparticles became stronger, enhancing the dispersion stability of the polishing liquid. As Figure 5 and Figure 6 shown, it can be seen that the morphology of Co-CeO2 changed after modification.

[0048] Example 2

[0049] Add 300ml of toluene to the flask, mix with 15ml of 50wt% ureapropyltriethoxysilane solution, and then ultrasonicate for 10min. Put the flask in a water bath, raise the temperature to 80℃, and stir mechanically at 200rpm for 15min. Finally, add 15g of Co-CeO2 to the flask and react for 8h. After the reaction, filter, wash with anhydrous ethanol and deionized water in turn, and vacuum dry to obtain an amino-modified cerium oxide powder, which is recorded as Co-CeO2-NH2. Mix 10g of Co-CeO2-NH2 nanoparticles with 2.5g of surfactant sodium stearate in 200ml of distilled water at a mass ratio of 4:1. After ultrasonication for 30 minutes, put the flask in a water bath, raise the temperature to 85℃, and stir mechanically at 200rpm for 8h. After the reaction, the product was filtered, washed with anhydrous ethanol and deionized water in turn, and dried in vacuo to obtain a dry powder, which was surfactant-modified cerium oxide, denoted as Co-CeO2-NH2-SS.

[0050] The first modified Co-CeO2-NH2 abrasive and the second modified Co-CeO2-NH2-SS abrasive were used in chemical mechanical polishing experiments. Co-CeO2-NH2-SS was dispersed by wet ball milling, and the pH was adjusted to 5 with KOH and acetic acid. The CeO2 abrasive concentration was measured to be 1wt%. The TEOS wafer was polished on a GNP polisher. The down pressure was 3psi, the back pressure was 0psi, the polishing head speed and the polishing disc speed were 100rpm, and the polishing liquid flow rate was 100ml / min. Figure 9 and Figure 10 As shown in the figure, it can be clearly seen that after one modification, the polishing rate of Co-CeO2-NH2 increased by nearly 30%. 3+ CeO2 can form Si-O-Ce bonds on the surface of silicon oxide during the polishing process of silicon oxide, and remove surface silicon under the action of mechanical grinding, so Ce 3+ The increase of content can effectively improve the polishing rate. Co-CeO2-NH2-SS abrasive presents the best surface quality. The improvement of surface quality is related to the reduction of abrasive particle size after modification and its more concentrated distribution.

[0051] Example 3

[0052] Add 300 ml of toluene into a flask, mix it with 15 ml of 50 wt% ureapropyltriethoxysilane solution, and then sonicate for 10 min. Place the flask in a water bath, raise the temperature to 80 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm for 15 min. Finally, add 15 g of Co-CeO2 into the flask and react for 8 h. After the reaction, filter, wash successively with absolute ethanol and deionized water, and vacuum dry the obtained dry powder, which is amino-modified cerium oxide, denoted as Co-CeO2-NH2. Mix 10 g of Co-CeO2-NH2 nanoparticles with 2 g of the surfactant sodium dodecyl sulfate in 200 ml of distilled water according to a mass ratio of 5:1. After sonication for 30 minutes, place the flask in a water bath, raise the temperature to 85 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm and react for 8 h. After the reaction, filter, wash successively with absolute ethanol and deionized water, and vacuum dry the obtained dry powder, which is surfactant-modified cerium oxide, denoted as Co-CeO2-NH2-SDS. As Figure 1 and Figure 7 shown, it indicates that the introduction of amino groups significantly enhances the interaction between surface hydroxyl groups and amino groups. After secondary modification, the surfactant containing sulfonate groups is highly enriched on the surface of Co-CeO2-NH2, further proving that the surfactant molecules are successfully grafted onto Co-CeO2-NH2.

[0053] Example 4

[0054] Add 300 ml of toluene into a flask, mix it with 15 ml of 50 wt% ureidopropyltriethoxysilane solution, and then ultrasonicate for 10 min. Place the flask in a water bath, raise the temperature to 80 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm for 15 min. Finally, add 15 g of Co-CeO2 into the flask and react for 8 h. After the reaction is completed, filter, wash successively with absolute ethanol and deionized water, and vacuum dry the obtained dry powder, which is amino-modified cerium oxide, denoted as Co-CeO2-NH2. Mix 10 g of Co-CeO2-NH2 nanoparticles with 2.5 g of surfactant sodium dodecyl sulfate in 200 ml of distilled water according to a mass ratio of 4:1. After ultrasonication for 30 minutes, place the flask in a water bath, raise the temperature to 85 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm and react for 8 h. After the reaction is completed, filter, wash successively with absolute ethanol and deionized water, and vacuum dry the obtained dry powder, which is surfactant-modified cerium oxide, denoted as Co-CeO2-NH2-SDS. Use the twice-modified Co-CeO2-NH2-SDS abrasive for chemical mechanical polishing experiments. Disperse Co-CeO2-NH2-SDS by wet ball milling, adjust the pH to 5 with KOH and acetic acid, and measure the CeO2 abrasive concentration to be 1 wt%. Polish the TEOS wafer on a GNP polisher. The down pressure is 3 psi, the back pressure is 0 psi, the rotational speed of the polishing head and the polishing pad is 100 rpm, and the flow rate of the polishing liquid is 100 ml / min. As Figure 11 shown, the modified abrasive significantly improves the dispersion stability and fluidity of the polishing liquid, thereby enhancing the uniformity and smoothness of the overall coating.

[0055] Example 5

[0056] Add 300 ml of toluene into a flask, mix it with 15 ml of 50 wt% ureidopropyltriethoxysilane solution, and then ultrasonicate for 10 min. Place the flask in a water bath, raise the temperature to 80 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm for 15 min. Finally, add 15 g of Co-CeO2 into the flask and react for 8 h. After the reaction is completed, filter, wash successively with absolute ethanol and deionized water, and vacuum dry the obtained dry powder, which is amino-modified cerium oxide, denoted as Co-CeO2-NH2. Mix 10 g of Co-CeO2-NH2 nanoparticles with 2 g of surfactant sodium lauryl polyoxyethylene ether sulfate in 200 ml of distilled water according to a mass ratio of 5:1. After ultrasonication for 30 minutes, place the flask in a water bath, raise the temperature to 85 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm and react for 8 h. After the reaction is completed, filter, wash successively with absolute ethanol and deionized water, and vacuum dry the obtained dry powder, which is surfactant-modified cerium oxide, denoted as Co-CeO2-NH2-AES. As Figure 8As shown, the surfactant containing phosphate groups ionizes anions, which attach to the surface of Co-CeO2-NH2, enhancing the electrostatic repulsion between particles. The morphology of Co-CeO2-NH2-AES abrasive changes.

[0057] Example 6

[0058] Add 300 ml of toluene to a flask, mix it with 15 ml of 50 wt% ureidopropyltriethoxysilane solution, and then sonicate for 10 min. Place the flask in a water bath, raise the temperature to 80 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm for 15 min. Finally, add 15 g of Co-CeO2 to the flask and react for 8 h. After the reaction, filter, wash successively with anhydrous ethanol and deionized water, and vacuum dry the obtained dry powder to obtain amino-modified cerium oxide, denoted as Co-CeO2-NH2. Mix 10 g of Co-CeO2-NH2 nanoparticles with 2.5 g of the surfactant sodium lauryl polyoxyethylene ether sulfate in 200 ml of distilled water at a mass ratio of 4:1. After sonication for 30 minutes, place the flask in a water bath, raise the temperature to 85 °C, and simultaneously carry out mechanical stirring at a speed of 200 rpm and react for 8 h. After the reaction, filter, wash successively with anhydrous ethanol and deionized water, and vacuum dry the obtained dry powder to obtain surfactant-modified cerium oxide, denoted as Co-CeO2-NH2-AES. Use the secondarily modified Co-CeO2-NH2-AES abrasive for chemical mechanical polishing experiments. Disperse Co-CeO2-NH2-AES by wet ball milling, adjust the pH to 5 with KOH and acetic acid, and measure the CeO2 abrasive concentration to be 1 wt%. Polish the TEOS wafer on a GNP polishing machine. The down pressure is 3 psi, the back pressure is 0 psi, the polishing head speed and the polishing pad speed are 100 rpm, and the polishing fluid flow rate is 100 ml / min. As Figure 12 shown, after secondary modification, the improvement in the abrasive polishing rate of Co-CeO2-NH2-AES is the most significant, with an overall increase of about 40% compared to the abrasive, which can be attributed to the enhanced wettability.

[0059] The surface quality of the wafer after polishing with the surface-modified cerium oxide abrasive is improved. The Co-CeO2-NH2-SS abrasive in Example 2 exhibits excellent polishing quality, with a surface roughness of 0.0383. The Co-CeO2-NH2-AES abrasive in Example 6 has the highest polishing rate, and the material removal rate is

[0060] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included within the protection scope of the present invention.

[0061] Matters not covered by this invention are well-known techniques.

Claims

1. A surface modification method of Co-CeO2 abrasive based on the synergy of silane coupling agent and surfactant, characterized in that, The method comprises the following steps: Step 1: Mix toluene with a silane coupling agent solution and then ultrasonicate for 10 - 30 min to obtain a first mixed solution; Among them, the volume ratio is that toluene : silane coupling agent solution = 15:1 - 25:1; the mass percentage concentration of the silane coupling agent solution is 40 - 60%; The silane coupling agent is ureidopropyltrimethoxysilane, mercaptopropyltrimethoxysilane or mercaptopropyltriethoxysilane; The surfactant is dialkyl sulfosuccinate, surfactant alkylsulfonatoacetate, hydroxyethyl sulfonate, sulfonated fatty acid methyl ester, oligoglycerol, oligomeric (ethylene glycol) ester of fatty acid, ester quaternary ammonium salt, sodium dodecyl sulfate, sodium lauryl polyoxyethylene ether sulfate, dodecyl phosphate or lauryl phosphate; Step 2: Under water bath, heat the first mixed solution to 80 - 100 °C and stir at this temperature for 15 - 20 minutes; Step 3: Then add Co - CeO₂ and react for 8 - 10 hours; Among them, 10 - 20 g of Co - CeO₂ is added to every 200 - 400 mL of the mixed solution; Step 4: After the reaction is completed, filter, wash and vacuum dry to obtain substance A; Substance A is Co - CeO₂ - NH₂ or Co - CeO₂ - SH; Step 5: Mix substance A with a surfactant in distilled water and ultrasonicate for 20 - 40 minutes to obtain a second mixed solution; Among them, the mass ratio of substance A to the surfactant is 4 - 5:1; 10 - 20 g of substance A and 2 - 4 g of the surfactant are added to every 200 ml of distilled water; Step 6: Under water bath again, heat the second mixed solution to 80 - 100 °C and stir at this temperature for 7 - 8 hours; Step 7: Filter, wash and vacuum dry to obtain the modified Co - CeO₂ abrasive.

2. The surface modification method of Co-CeO2 abrasive based on the synergy of silane coupling agent and surfactant as claimed in claim 1, characterized in that, The stirring speed in Step 2 is 150 - 200 rmp.

3. The surface modification method of Co-CeO2 abrasive based on the synergy of silane coupling agent and surfactant as claimed in claim 1, characterized in that the steps The washing in Steps 4 and 7 is to wash successively with absolute ethanol and deionized water.

4. Use of the Co-CeO2 abrasive prepared by the method according to claim 1, characterized in that it is used for Polishing of the SiO₂ dielectric layer.

5. The application according to claim 4, characterized in that, Comprises the following steps: (1): Wet - ball - mill and disperse Co - CeO₂ - NH₂ - SS, and adjust the pH to 5 - 6 with KOH and acetic acid to obtain a CeO₂ abrasive concentration of 0.5 - 1.5 wt%; (2): Polish the TEOS wafer on a GNP polishing machine; among them, the down - pressure is 2 - 4 psi, the back - pressure is 0 psi, the rotational speed of the polishing head and the polishing pad is 50 - 150 rpm, and the flow rate of the polishing liquid is 100 - 200 ml / min.

Citation Information

Cited By

  • Acid polishing solution for dielectric layer as well as preparation method and application of acid polishing solution

    CN121851908A

  • An acidic polishing solution for dielectric layers, its preparation method and use

    CN121851908B